Reverse supply chains issues and analysis - Gupta, Surendra M. (CRC Press, 2013)
"Reverse supply chains consist of a series of activities required to collect used products from consumers and reprocess them to either recover their leftover market values or dispose of them. It has become common for companies involved in a traditional (forward) supply chain (series of activities required to produce new products from virgin materials and distribute them to consumers) to also carry out collection and reprocessing of used products (reverse supply chain). Strict environmental regulations and diminishing raw material resources have intensified the importance of reverse supply chains at an increasing rate. In addition to being environment friendly, effective management of reverse supply chain operations leads to higher profitability by reducing transportation, inventory and warehousing costs. Moreover, reverse supply chain operations have a strong impact on the operations of forward supply chain such as the occupancy of the storage spaces and transportation capacity"--Vydavatelská anotace